Life Cycle Cost-Orientated Service Models for Tool and Die Companies - Schuh, G.; Boos, W.; Kozielski, S. (Cranfield University Press, 2009)
As the success of a company’s service provision is founded in its business model, the latter needs to be redesigned to align strategic and operational objectives. Therefore at RWTH Aachen University a new approach to service models for the European tooling industry links products and services by means of a direct calculation of life cycle costs. Tool and die makers are enabled to offer product-service-systems, which allow expanding the range of service provision by directly addressing the cost-effectiveness of the whole product-service-system. Hence the minimisation of life cycle costs of tools and dies can be used as a new sales pitch for services in this unique industry.
Organised by: Cranfield University
Keywords: Business Models; Product-Service-Systems; Tool and die making; Life Cycle Costing